Body growth in primary de Toni-Debré-Fanconi syndrome - Haffner, Dieter; Weinfurth, Achim Michael; Seidel, Christoffer; Manz, Friedrich; Schmidt, Hildgund; Waldherr, Rüdiger; Bremer, Hans J.; Mehls, Otto; Schärer, Karl (Pediatric nephrology, 1997)
.Body growth in nine children with primary de Toni-Debré-Fanconi syndrome was followed from birth to adolescence or adult life. At the time of diagnosis, corresponding to the start of treatment, the median age was 2.3 (range 0.4-13.9) years and height standard deviation score (SDS) was always decreased (median -3.5, range -6.8 to -2.1). Despite continuous electrolyte and bicarbonate supplementation only four patients showed a slight improvement in growth. At the time of the last observation at the age of 17.2 (4.5-20.1) years median height was -4.7 (-5.9 to -1.8) SDS. The median difference between height at last observation and target height was -4.5 SDS. Final height (n=5) ranged between -1.8 and -5.5 (median -4.3) SDS. The pubertal growth spurt was absent in two children. Metabolic acidosis was identified as a significant growth-retarding factor. Mean serial blood bicarbonate levels and height SDS at the last observation were correlated (r=-0.87, P<0.01). No correlation was observed between last height SDS and the degree of hypokalemia, hypophosphatemia, or hypercalciuria. In conclusion, patients with primary de Toni-Debré-Fanconi-syndrome present severe growth failure at the time of diagnosis which persists into adult life. Supportive therapy is frequently unable to prevent further loss of relative height.